2018
DOI: 10.1039/c8ra03107j
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the intramolecular C–H⋯O interactions on the conformational preferences of bis-arylsulfones – 5-HT6receptor antagonists and beyond

Abstract: The development of compounds with enhanced activity and selectivity by a conserved spatial orientation of the pharmacophore elements has a long history in medicinal chemistry. Rigidified compounds are an example of this concept. However, the intramolecular interactions were seldom used as a basis for conformational restraints. Here, we show the weak intramolecular interactions that contribute to the relatively well-conserved geometry of N1-arylsulfonyl indole derivatives. The structure analysis along with quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
2
5
0
Order By: Relevance
“…Some work reported that the QTAIM analysis is not able to detect all expected weak noncovalent interactions, , which is also found in this work. As shown in Figure , SGD adopts conformation 1 in SGD·H 2 O, SGD-3NBA, SGD-PHE, SGD-PT, and SGD-TBA·2H 2 O, generating S(6) and S(5) rings.…”
Section: Resultssupporting
confidence: 77%
“…Some work reported that the QTAIM analysis is not able to detect all expected weak noncovalent interactions, , which is also found in this work. As shown in Figure , SGD adopts conformation 1 in SGD·H 2 O, SGD-3NBA, SGD-PHE, SGD-PT, and SGD-TBA·2H 2 O, generating S(6) and S(5) rings.…”
Section: Resultssupporting
confidence: 77%
“…2A–C ; 3A ). The presence of such intramolecular interactions results in favorable protein–ligand orientation, leading to high binding affinity [ 42 ]. The high number of intramolecular interactions between the protein and ligand stabilizes the geometry of two interacting molecules [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed to be a complex mechanism and is associated with symptoms such as ischemic stroke, pyramidal signs, hypo/anosmia, delirium, and impaired consciousness [ 6 ]. However, it should be noted that the neurological consequences of SARS-CoV-2 may be secondary to the manifestations of hypoxia and ARDS [ 7 ]. It has already been reported that hypoxia and ARDS can be the neurological disorders of COVID-19 progression [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicated that compounds containing unsubstituted phenylsulfonyl moiety are highly potent 5-HT6R ligands, whereas their benzyl analogs require substitution with a chlorine atom in the meta position. 35 To achieve inhibition of MAO-B activity, aryloxy fragments derived from rasagiline, safinamide and pargyline were linked to the 5-HT6R pharmacophore via different length alkylene linker. Although the molecular framework of the designed hybrids is different from that of classical MAO-B inhibitors (they are very long, with two basic centers and a flexible alkylene linker), the possibility of interaction with the catalytic domain of MAO-B was supported by in silico experiments.…”
Section: Structure-activity Relationship Studiesmentioning
confidence: 99%